1999
DOI: 10.1080/07391102.1999.10508316
|View full text |Cite
|
Sign up to set email alerts
|

NMR Structures of a Nonapeptide from DNA Binding Domain of Human Polymerase-α Determined by Iterative Complete-Relaxation-Matrix Approach

Abstract: Nuclear magnetic resonance structures of a nonapeptide, ERFKCPCPT, selected from the DNA binding domain of human polymerase-alpha, were determined by complete relaxation matrix analysis of transverse NOE data. The structures exhibit a type III turn with residues KCPC, and the remaining residues exhibit non-ordered structures. The turn was confirmed by alpha, N (i,i+3) connectivity, a low temperature coefficient of NH chemical shift (-3.1 x 10(-3)) of the fourth residue, 3J(NHalpha) coupling constants, and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Finally, it was shown that cis-platin binds to thiols much stronger than it binds with guanine [51]. This led to the hypothesis that cis-platin inhibits DNA polymerase-α by binding to the zinc-binding domain, displacing the zinc, and perturbing the structure of the domain [52,53]. It is thought the enzyme recognizes the DNA substrate through the zinc-binding domain, so structural perturbation may interfere with the ability of the enzyme to recognize its substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it was shown that cis-platin binds to thiols much stronger than it binds with guanine [51]. This led to the hypothesis that cis-platin inhibits DNA polymerase-α by binding to the zinc-binding domain, displacing the zinc, and perturbing the structure of the domain [52,53]. It is thought the enzyme recognizes the DNA substrate through the zinc-binding domain, so structural perturbation may interfere with the ability of the enzyme to recognize its substrate.…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that cisplatin binds to the Zn-binding domain of DNA polymerase-α approximately 1000 times stronger than binding to guanine [52]. Structural studies of the Zn-binding domain of DNA polymerase-α have shown that divalent Pt (II) binds, to vicinal cysteine residues within the protein [53]. These studies have led to the hypothesis that during cis-platin induced apoptosis, in addition to DNA degradation by DFF, synthesis of DNA may also be inhibited.…”
Section: Introductionmentioning
confidence: 94%
“…cis-platin is proved to be inhibiting DNA polymerase-alpha [47] and the Helicase III [18,48] in these breast carcinoma cells. It is also established that cis-platin binds to the Zn-binding domain in the active site of DNA polymerase-alpha [49,50]. The exact relation of the inactivation of the replication complex and initiation of apoptotic process is not known [17,48].…”
Section: Discussionmentioning
confidence: 99%